2021
DOI: 10.1007/s12630-021-02100-4
|View full text |Cite|
|
Sign up to set email alerts
|

The association of prothrombin complex concentrates with postoperative outcomes in cardiac surgery: an observational substudy of the FIBRES randomized controlled trial

Abstract: Purpose The mainstay of therapy for coagulation factor deficiency in cardiac surgical patients is frozen plasma (FP); however, prothrombin complex concentrates (PCCs) may offer logistical and safety advantages. As there is limited comparative evidence, we conducted this study to explore the association of comparable PCC or FP doses with transfusion and outcomes. Methods This was a post hoc analysis of a multicentre randomized trial comparing fibrinogen concentrate with cryoprecipitate (FIBRES trial) in bleedin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…2 Past work has demonstrated pronounced increases in systemic thrombin generation after major trauma, which continues to increase during the initial hours and days after injury, making many patients profoundly hypercoagulable. 3,4 This, combined with ongoing antithrombin inhibition through thrombin-mediated consumption or neutrophil elastase release, as observed in this study, could explain why higher antithrombin levels are linked with VTE in this population (and even higher levels may be required to prevent these events).…”
Section: Targeting Chemoprophylaxis In Venous Thromboembolism Using B...mentioning
confidence: 58%
See 2 more Smart Citations
“…2 Past work has demonstrated pronounced increases in systemic thrombin generation after major trauma, which continues to increase during the initial hours and days after injury, making many patients profoundly hypercoagulable. 3,4 This, combined with ongoing antithrombin inhibition through thrombin-mediated consumption or neutrophil elastase release, as observed in this study, could explain why higher antithrombin levels are linked with VTE in this population (and even higher levels may be required to prevent these events).…”
Section: Targeting Chemoprophylaxis In Venous Thromboembolism Using B...mentioning
confidence: 58%
“…Use of a fixed-dose approach to VTE chemoprophylaxis was criticized over a decade ago when the landmark PROTECT II trial, powered for superiority, surprisingly demonstrated similar rates of VTE development in critically ill patients receiving dalteparin vs unfractionated heparin. 3,4 Underdosing is seen in Vincent et al 1 because neither cohort consistently demonstrated therapeutic anti-Factor Xa (FXa) levels and that it took a significantly longer duration to achieve therapeutic levels in the VTE group. Although antithrombin supplementation can improve the response to heparin in the setting of lower anti-FXa levels, 5 lower anti-FXa levels could be avoided by providing adequate weight-based dosing.…”
Section: Targeting Chemoprophylaxis In Venous Thromboembolism Using B...mentioning
confidence: 99%
See 1 more Smart Citation
“…9 An additional observational investigation in postcardiac surgery bleeding compared 415 patients who received either PCC only (n = 72) or FFP only (n = 343). 31 The primary outcome assessment included RBC and platelet transfusion needs in the first 24 hours after bypass. The analysis demonstrated that each unit of FFP was associated with an increase in odds of RBC and platelet transfusion; whereas every 500 units of PCC were associated with a decrease in the odds of RBC and platelet transfusion.…”
Section: Prothrombin Complex Concentratesmentioning
confidence: 99%
“…Next, Santana et al [22] review the use of PCC in cardiac surgery. They present mechanistic background information, followed by a review of retrospective studies and the handful of prospective clinical trials that demonstrate decreased red blood cell transfusion and more rapid haemostatic correction compared to fresh frozen plasma [23,24]. However, there are currently no data to adequately determine if their use impacts other clinically meaningful outcomes.…”
mentioning
confidence: 99%